2020
DOI: 10.1155/2020/8852156
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity and Size of Choroidal Neovascularization in Highly Myopic Eyes with a Dome-Shaped Macula

Abstract: Introduction. A dome-shaped macula (DSM) is an inward convexity or anterior deviation of the macular area. DSM is believed as a protective factor in maintaining visual acuity in highly myopic eyes. Objective. To investigate the correlation between best-corrected visual acuity (BCVA), choroidal neovascularization (CNV), and a dome-shaped macula (DSM) in highly myopic eyes. Methods. In this retrospective and observational case series study, BCVA tests and optical coherence tomography (OCT) were performed in a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Of note, the number of recurrences per eye possible that, as symptoms mostly occur when the fovea is involved, the diagnosis of CNV in DSM eyes may have been delayed, explaining their larger neovascular nets. 23 In our cohort, the dimension of the CNV was not statistically different between the two groups, thus suggesting a relatively early detection of the extrafoveal lesions in DSM eyes. This could be the result of a selection bias as highly myopic patients undergo routine ophthalmic examination in our tertiary referral center regardless of the presence of visual symptoms; hence, they may not well represent the general population of DSM, thus leading to a possible overestimation of extrafoveal CNVs.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Of note, the number of recurrences per eye possible that, as symptoms mostly occur when the fovea is involved, the diagnosis of CNV in DSM eyes may have been delayed, explaining their larger neovascular nets. 23 In our cohort, the dimension of the CNV was not statistically different between the two groups, thus suggesting a relatively early detection of the extrafoveal lesions in DSM eyes. This could be the result of a selection bias as highly myopic patients undergo routine ophthalmic examination in our tertiary referral center regardless of the presence of visual symptoms; hence, they may not well represent the general population of DSM, thus leading to a possible overestimation of extrafoveal CNVs.…”
Section: Discussionmentioning
confidence: 47%
“…Baseline CNV areas were similar in the two groups ( P = 0.112), and there were no significant changes in the 24-month follow-up period in DSM ( P = 0.163) and non-DSM ( P = 0.215) eyes. In a series of 40 eyes with myopic CNV, Wang et al 23 identified 13 eyes with DSM which had worse BCVA and larger lesions when compared with non-DSM eyes at disease presentation. It is possible that, as symptoms mostly occur when the fovea is involved, the diagnosis of CNV in DSM eyes may have been delayed, explaining their larger neovascular nets.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al reported that there were no differences in visual and CRT improvement for mCNV with and without a DSM after anti‐VEGF treatment for 1 year 18 ; however, in their study, patients without DSM showed greater reduction of CRT in the first month, which might imply that patients without a DSM might be more sensitive to the anti‐VEGF treatment at the early stage. Wang et al reported that eyes with CNV in the DSM group had a larger CNV area than those in the non‐DSM group, 19 so the VEGF level might be higher in DSM eyes with CNV, which might lead to more risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…3 Dome-shaped macula (DSM) was first described by Gaucher and coworkers in 2008 who observed a dome-shaped elevation on OCT within the region of a posterior staphyloma (PS) seen exclusively in highly myopic eyes. 16 It was initially thought to be an inward bulging of the sclera, but was later proven to be caused by a localized thickening of sclera by Imamura et al 17 The focal area of increased scleral CNV area than those in the non-DSM group, 19 so the VEGF level might be higher in DSM eyes with CNV, which might lead to more risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have observed other complications in eyes with DSM, such as foveoschisis, serous retinal detachment and choroidal neovascularisation, which may exacerbate visual impairment in myopic eyes. [5][6][7][8] Recent studies have shown that DSM is associated with a lower incidence of myopic foveoschisis, 3 and that a higher DSM appears to have a preventive effect on the development of foveoschisis. 9 However, the relationship between myopic complications and DSM remains uncertain.…”
Section: Introductionmentioning
confidence: 99%